Educating Youth Against Tobacco Advertising: A Media Literacy Approach for Reducing Indonesia's Replacement Smokers - Santi Indra Astuti (Pusat Penerbitan Universitas (P2U) LPPM Unisba, 2017)
According to recent data extracted from Global Tobacco Atlas (2015), about 66% Indonesian male aged no less than 15 years old are active smokers. It means 2 among 3 Indonesian male are smokers. The number of young smokers arose significantly. Smokers among 15-19 years old has increased 17 % each year, meanwhile, baby smokers among 5-9 years old has multiplied 400 %. These figures implied the rise of health risk among Indonesians. The tobacco industry tries every year to recruit young people to replace those current smokers who are dying or quitting. This youth being targeted by tobacco industry is called ‘replacement smokers’, and is lured to start smoking through the work of advertising and creative marketing strategy. A study carried out by Health Ministry of Indonesia showed that 70% youth were started to smoke after heavily exposed by cigarette advertising. In order to break tobacco advertising spell, a brand jamming strategy based on media literacy approach was conducted toward junior high school pupils. By educating them about advertising-behind-the scene and challenging them to creatively produce a ‘mocking’ version of popular tobacco ads, students now are capable enough to deconstructing the real message behind tobacco ads.